Soil Characteristics in Relation to Vegetation and Parent Material under Different Forest Covers in Kempty forest Range, Uttarakhand - Raina, A. K.; Gupta, M. K. (Indian Forester, 2009)
Soil characteristics in relation to Forest vegetation and parent material in Kempty range of Mussoorie Forest Division, Uttarakhand have been studied. The results show that geologically, the rocks of the study area are of pre-cambrian to early paleozoic in age with recent and subrecent deposits. The organic matter and available nitrogen contents in the surface horizons increased with increase in altitude. The increase in the clay content of B horizon may be due to in-situ weathering of minerals. From the clay content of different horizons, it is quite evident that movement of clay from A to B horizon has taken place in all the profiles. Due to clay illuviation and greater thickness of B horizon, soils from Sainj, Kempty and Mailgarh blocks having Pinus roxburghii, Quercus leucotrichophora and Dalbergia sissoo vegetation, respectively, appeared to be more developed than those from Kheragarh and Gandiyala blocks (Miscellaneous and barren land). Statistical analysis showed that source of variations in different soil characteristics are significant for Clay, pH, CEC, Ex. Na, Available N and WHC for replications It has been observed that Q. leucotrichophora and P. roxburghii forests occur in the soils of Mollisols order on limestone, dolomite, shale, slate and quartzite (Kempty and Sainj blocks) whereas presence of phyllite (Mailgarh and Kheragarh blocks) shale, sandstone, quartzite etc. resulted in Ultisols order. The barren land soil of Gandiyala block belonged to Mollisols order. Findings of the study will be helpful to formulate the strategies for sustainable management of the natural forests and to work out potential productivity of soil and forest etc. for the overall afforestation of such lands and to create deeper understanding of natural stands ensuring ecological and economic benefits reaching the rural masses.